Comparative Trials of 5% Permethrin Lotions Vs 1% Gamma Benzene Hexachloride Lotions in Treatment of Scabies (Journal of Nobel Medical College, 2018)
Background: Scabies is a contagious pruritic skin condition caused by the mite Sarcoptesscabiei var. hominis, and it is one of the major public health problem in developing country like ours. To determine and compare the efficacy of topical permethrin and topical gamma benzene hexachloride in treatment of scabies in population of Nepal.Methods: This was a prospective, randomized, comparative study conducted in 300 diagnosed cases of scabies treated with permethrin and gamma benzene hexachloride.Results: At the end of 2nd week, treatment was effective in 91.2% cases in permethrin (group A) and 64.6% in gamma benzene hexachloride (group B). After switch over of the non-improved patients to the other group drug, 6.7% were treated successfully with gamma benzene hexachloride and 80.9% were treated successfully with permethrin at the end of 4th week. No major side effects were observed in both groups. Gamma benzene hexachloride was found to be cost effective than permethrin.Conclusion: Permethrin was found to be more effective than gamma benzene hexachloride in treatment of scabies.